PENGARUH PEMBERIAN KREDIT USAHA RAKYAT TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN LUWU UTARA - Rahmadani, Rezki; Hadrah, Hadrah; Jusman, Jusman (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The aim of this research is to determine the effect of providing people's business credit (KUR) on the performance of UMKM in North Luwu Regency. This research uses a qualitative method with a descriptive approach. The sampling technique used purportive sampling, the analysis method used was simple regression analysis. The research findings indicate that the provision of KUR (Kredit Usaha Rakyat, or People's Business Credit) has a positive and significant impact on the performance of UMKM (Micro, Small, and Medium Enterprises) in Luwu Regency. The study demonstrates that access to KUR financing has enhanced the operational efficiency, growth, and sustainability of local UMKM, helping them overcome financial constraints and improve their overall business performance. This highlights the importance of targeted financial support for small businesses, particularly in rural areas, to drive economic development and entrepreneurship.